Nanostructured tungsten oxide gas sensors prepared by electric field assisted aerosol assisted chemical vapour deposition - Michael Warwick (J. Mater. Chem. A, 2013)
Nanostructured thin films of tungsten trioxide were deposited on to gas sensor substrates at 600 °C from the aerosol assisted chemical vapour deposition reaction of tungsten hexaphenoxide solutions in toluene under the influence of electric fields. The electric fields were generated by applying a potential difference between the inter-digitated electrodes of the gas sensor substrates during the deposition. The deposited films were characterised using scanning electron microscopy, X-ray diffraction and Raman spectroscopy. The application of an electric field, encouraged formation of enhanced nanostructured morphologies, with an increase in needle length and reduction in needle diameter being observed. The film gas sensor properties were also examined; it was found that the highest response of 110 to 800 ppb NO2 was given by a sensor grown under the influence of a 1.8 × 104 V m−1 electric field and operated at 250 °C, a 2.5 times enhancement compared to a sensor grown in the absence of an electric field under its optimal operating conditions.